Targeting ferroptosis with natural products in stroke: therapeutic mechanisms and translational opportunities - Zheng, Yingyi; Tan, Xi; Wang, Xiaojie; Mao, Rui; Guo, Jianwen (Frontiers in Pharmacology, 2025)
Ferroptosis is a new type of controlled cell death. It is distinguished by its reliance on iron and the production of lipid peroxidation. The role of ferroptosis in stroke has attracted a lot of attention recently. The purpose of this review is to clarify the connection between ferroptosis and stroke and to investigate the potential contribution of natural products to the clinical management of stroke and the discovery of novel medications. In this review, we summarize in detail the mechanism of ferroptosis after stroke, especially the relevant targets of ferroptosis after stroke. Furthermore, we summarize the natural products and herbal medicine currently employed in ferroptosis along with their mechanisms of action, highlighting the potential and challenges of clinical translation. We included 55 articles and classified them. After systematic screening, We think that ginkgolide B, kellerin, loureirin C, quercetin, icariside II, salvianolic acid A, berberine, Dl-3-n-butylphthalide is an effective candidate drug for the treatment of stroke.